FAKTOR FAKTOR YANG MEMPENGARUHI INFLASI SERTA DAMPAKNYA PADA PENGANGGURAN DAN KEMISKINAN DI KOTA PANGKALPINANG - Hamdan .; Afrizal . (LPPM STIE PERTIBA Pangkalpinang, 2017)
This study aims to analyze the influence of transportation, the number of tourist visits and the amount of Inflation either simultaneously or partially. Furthermore, to analyze the effect of inflation on unemployment and poverty level. The type of data used in this study is secondary data in Pangkalpinang city. The data analyzed in the form of time series in the period 2005 - 2017. Research data is analyzed by regression analysis technique, the processing is done through Eviews software.The result of this research is there are a positive influence and not significant simultaneously transportation, number of tourist visit and amount of population to inflation. Partially that transportation and tourist visit can decrease inflation while population can raise the inflation rate